Algernon Brashear Jackson, M.D.: A Pioneer for Community and Minority Advocacy. Issue 6 (June 2018) - Lundy, Megan E.; Cowan, Scott W.; Yeo, Charles J.; Lazar, Melissa
A historical vignette regarding Dr. Algernon Brashear Jackson, the first Black male graduate from Jefferson Medical College. It details his early life, medical school years, surgical training, and contributions to his local community and beyond as he paved the way for future doctors of color.